PENYEDIAAN AKSES LEGAL DAN AMAN UNTUK ABORSI DI INDONESIA - Nita Ariyani (UIR Law Review, 2023)
Abortion is regulated internationally especially in the ICCPR, CEDAW and ICESCR. Indonesia also regulates abortion based on Law No. 1 of 2023 concerning the Criminal Code, Law No. 17 of 2023 concerning Health, Government Regulation No. 61 of 2014 concerning Reproductive Health, and Regulation of Minister of Health No. 3 of 2016.  The practice of safe abortion services until now is difficult for victims of sexual violence to access, in practice there are still many obstacles from a systematic and structural perspective when victims want to access legal abortions This research aims to examine the regulations in national law and international law related to providing legal and safe access to abortion for women and the implementation of providing legal and safe access to abortion in Indonesia.This research uses normative juridical with statute approach, and case approach. This research contains the legality of abortion in national law and international law and the obstacles faced in providing access to legal and safe abortion. Indonesia has ratified CEDAW, ICCPR and ICESCR regarding providing access to legal, safe and effective abortion in order to realize equality in health services, so the state must take firm actions in order to realize the legal and safe abortion services needed by women and girls.